2005
DOI: 10.1002/mc.20151
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic changes associated with DYNACTIN‐2 (DCTN2) over expression characterise SJSA‐1 osteosarcoma cells

Abstract: DYNACTIN-2 (DCTN2) localises to chromosome 12q13-q15, a region prone to stable amplification in several cancers. Transient DCTN2 overexpression has a significant impact on cellular phenotype primarily due to disruption of the DYNEIN-dynactin motor. Changes reported include alterations of microtubule-directed movement of molecular (e.g. TP53) and organelle (e.g. Golgi) cargoes towards the nucleus, centrosome biology, cellular movement and mitosis with a potential predisposition to mitotic block and polyploidy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Overexpression in mammalian cells of one dynactin subunit (dynamitin) disrupts the complex, resulting in the perturbation of mitosis (32). In addition, DCTN2 overexpression disrupt the dynein-dynactin motor, shifting cellular movement and mitosis with predisposition to mitotic block and polyploidy (33). DCTN3 localizes to the centrosomes during interphase and to kinetochores and spindle poles throughout mitosis.…”
Section: Dctn3 and Rhbdd2 As Predictors Or Recurrencementioning
confidence: 99%
“…Overexpression in mammalian cells of one dynactin subunit (dynamitin) disrupts the complex, resulting in the perturbation of mitosis (32). In addition, DCTN2 overexpression disrupt the dynein-dynactin motor, shifting cellular movement and mitosis with predisposition to mitotic block and polyploidy (33). DCTN3 localizes to the centrosomes during interphase and to kinetochores and spindle poles throughout mitosis.…”
Section: Dctn3 and Rhbdd2 As Predictors Or Recurrencementioning
confidence: 99%
“…These studies demonstrated that DCTN1 acted as a fusion partner in non-small cell lung cancer (NSCLC), 17 and DCTN2 was up-regulated in the osteosarcoma SJSA-1 cell line. 18 Another study showed that high expression of DCTN4 was significantly related to a favorable prognosis in colon adenocarcinoma (COAD) patients. 19 Moreover, it was reported that the mRNA expressions of down-regulated DCTN1 , DCTN2 , DCTN5 , and the up-regulated DCTN6 were associated with a satisfactory prognosis for cutaneous melanoma.…”
Section: Introductionmentioning
confidence: 99%
“… 30 DCTN2 was observed to be over expressed in SJSA-1 osteosarcoma cells. 31 Nevertheless, the correlation between DCTN4 and cancer was not stated. Here, we have employed statistics from TCGA on expression and medical data in COAD to investigate correlations between DCTN gene family expression levels and prognosis and to identify biomarkers that can be used for prognosis and diagnosis in patients with COAD.…”
Section: Discussionmentioning
confidence: 99%